(untitled) (Szociológiai Szemle, 2024)
Status inconsistency was a typical feature of communist societies. Hungary was also characterised by a low correlation between status measures like occupation, education, income on the one hand, and cultural or material life style on the other. The paper investigates the changing effects of demographic (sex, age, region) socioeconomic (prestige, education, income), and class (service and entrepreneurial class) measures on cultural and material consumption over one and half decades. Cultural consumption is measured by the number of books, visiting theatre, museum, concerts. Material consumption is measured by possessing various consumers durable (colour tv, refrigerator, automatic washing machine, car) in the household.